ANALYSIS OF ASH CONTENT, MACRO- AND MICROELEMENTS IN THE AERIAL PARTS OF THE ASPERUGO PROCUMBENS PLANT. (Scientific journal of the Fergana State University, 2025)
Asperugo procumbens is a widely distributed medicinal plant used in traditional medicine in the Middle East, but it is currently underrepresented in European pharmacopoeias. The aim of this study is to provide a detailed review of the Asperugo procumbens plant based on modern data in botany, traditional medicine, phytochemistry, and pharmacology. This article presents the general botanical description of Asperugo procumbens, its use in folk medicine, and its distribution. Information is provided on the ash content and the macro- and microelements present in the above-ground part of the plant. The scientific literature was gathered from open databases such as PubMed, Web of Science, Scopus, Google, Google Scholar, as well as from monographs and PhD dissertations. For the first time, a sample of the plant was collected from Okjar village, Dangara district, Fergana region, Uzbekistan, and an analysis of its above-ground part was conducted. It was found that the above-ground part of the plant contains essential macro- and microelements for the human body, such as K, Ca, Fe, Mg, P, and S. The total ash residue was 12.54% in the leaves and 13.24% in the stem, which confirms the potential use of this plant for the production of biologically active supplements and dietary additives.